2017
DOI: 10.1063/1.4977229
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Ni addition on microstructure and soft magnetic properties of FeCoZrBCu nanocrystalline alloys

Abstract: (Fe0.7Co0.3-xNix)88Zr7B4Cu1 nanocrystalline alloys were developed with the aim of improving the magnetic properties while keeping high Curie temperature (TC). It was revealed that Ni addition inhibited the precipitation of metastable fcc-(Fe,Co,Ni) phase hence increased thermal stability. Although the saturation magnetic flux density (Bs) showed a slight decrease, uniform nanostructure with small grain size and high volume fraction of crystals was formed with increasing Ni addition. As a result, the (Fe0.7Co0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 20 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…The ball detaches from the container wall when the value of the contact force is zero. The takeoff time can be estimated by applying the following expression [33]: t t = (1/(Ω + ω)) arccos (−(ω 2 r/Ω 2 R)), (6) In the P7 device this time is t t = 0.076 s. Likewise, the flight time t f (between detachment and collision) is also linked to the period (inverse of the frequency) in planetary mills. Thus, the period is higher in P7.…”
Section: Mills Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…The ball detaches from the container wall when the value of the contact force is zero. The takeoff time can be estimated by applying the following expression [33]: t t = (1/(Ω + ω)) arccos (−(ω 2 r/Ω 2 R)), (6) In the P7 device this time is t t = 0.076 s. Likewise, the flight time t f (between detachment and collision) is also linked to the period (inverse of the frequency) in planetary mills. Thus, the period is higher in P7.…”
Section: Mills Comparisonmentioning
confidence: 99%
“…There are soft magnetic offering reduced core losses over a wide range of applied frequencies. These alloys are an alternative for industrial (automotive, green energy) applications: High precision energy meters, absorber cores for suppression of motor bearing currents, high frequency current transformers, push-pull transformers for power transistors, and current sensors [3,4,6]. Due to magnetocaloric effect of the ferromagnetic to paramagnetic transition, these materials have also been of interest for magnetic refrigeration [7].…”
Section: Introductionmentioning
confidence: 99%
“…12 , et al have reported the effect of Ni addition on microstructure and soft magnetic properties of nanocrystalline alloys of (Fe 0.7 Co 0.3-x Ni x ) 88 Zr 7 B 4 Cu 1, where x=0, 0.1, 0.2, and 0.3. The results show that the substitution of Ni for Co increases the thermal stability and reduces the magneto-crystalline anisotropy.…”
mentioning
confidence: 99%